2019
DOI: 10.1177/0960327119883409
|View full text |Cite
|
Sign up to set email alerts
|

Prucalopride inhibits lung cancer cell proliferation, invasion, and migration through blocking of the PI3K/AKT/mTor signaling pathway

Abstract: Lung cancer is the main cause of cancer incidence and mortality around the world. Prucalopride is an agonist for the 5-hydroxytryptamine 4 receptor, but it was unknown whether prucalopride could be used to treat lung cancer. To investigate the biological effects of prucalopride on proliferation, apoptosis, invasion, and migration of lung cancer cells, and its underlying molecular mechanism in the progression of lung cancer, we performed this study. The Cell Counting Kit 8 assay was used to measure the prolifer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…The PI3K/mTOR signaling pathway facilitates the proliferation, invasion/migration, vascularization, and tumorigenicity of cancer cells [24][25][26][27]. si-TGF-β treatment markedly attenuated p-PI3K and p-Akt expression in U2OS and MG-63 cells (Figure 5(a)), indicating that the PI3K/mTOR signaling pathway may mediate the effects of TGF-β on osteosarcoma progression.…”
Section: Tgf-β Accelerates Osteosarcoma Progression Through Pi3k/mtor Signaling Pathway Activationmentioning
confidence: 99%
“…The PI3K/mTOR signaling pathway facilitates the proliferation, invasion/migration, vascularization, and tumorigenicity of cancer cells [24][25][26][27]. si-TGF-β treatment markedly attenuated p-PI3K and p-Akt expression in U2OS and MG-63 cells (Figure 5(a)), indicating that the PI3K/mTOR signaling pathway may mediate the effects of TGF-β on osteosarcoma progression.…”
Section: Tgf-β Accelerates Osteosarcoma Progression Through Pi3k/mtor Signaling Pathway Activationmentioning
confidence: 99%
“…Increasing evidence confirmed that the phosphoinositide 3-kinase/protein kinase B (PI3K/Akt) signaling pathway, as a regulatory factor of tumor progression, was activated in various cancers ( 15 , 16 ). For example, inhibition of the PI3K/Akt signaling pathway suppressed cell proliferation, invasion and migration of colorectal cancer ( 17 ), lung cancer ( 18 ), oral squamous cell carcinoma ( 19 ), hepatocellular carcinoma ( 20 ) and ESCC ( 21 ), etc. Moreover, several tumor-related genes (TRE), as the upstream regulator of the PI3K/Akt signaling pathway, were involved in tumor progression and development via regulating cancer cell malignant biological behavior, for instance, upregulation of gene of phosphate and tension homology deleted on Chromosome 10 (PTEN) inhibited tumor progression and enhanced the sensitivity of cancer cell to chemotherapy through blocking the PI3K/Akt signaling pathway ( 22 , 23 ).…”
Section: Introductionmentioning
confidence: 99%
“…Lung cancer is the leading cause of cancer‐related deaths across the world, imposing a huge burden on healthcare systems in every country 25 . An increasing number of researchers have highlighted the importance of EVs in several lung diseases 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Lung cancer is the leading cause of cancer-related deaths across the world, imposing a huge burden on healthcare systems in every country. 25 An increasing number of researchers have highlighted the importance of EVs in several lung diseases. 26 In the current study, we aimed to investigate whether EV-delivered miR-328-3p derived from hypoxic BMSCs influences the occurrence and progression of lung cancer and to uncover evidence demonstrating its novel tumour promoting role.…”
Section: Discussionmentioning
confidence: 99%